2021
DOI: 10.5271/sjweh.3987
|View full text |Cite
|
Sign up to set email alerts
|

Job strain and effort-reward imbalance as risk factors for type 2 diabetes mellitus: A systematic review and meta-analysis of prospective studies

Abstract: Job strain and effort-reward imbalance as risk factors for type 2 diabetes mellitus: A systematic review and meta-analysis of prospective studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Results of the present study are in line with previous literature, which reported a stronger and more consistent association between psychosocial stressors at work and T2DM among women (8, 13). A recent systematic review and meta-analysis evaluated the effect of ERI on T2DM incidence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results of the present study are in line with previous literature, which reported a stronger and more consistent association between psychosocial stressors at work and T2DM among women (8, 13). A recent systematic review and meta-analysis evaluated the effect of ERI on T2DM incidence.…”
Section: Discussionsupporting
confidence: 93%
“…Previous evidence suggests that psychosocial stressors at work are associated with an increased risk T2DM (7, 8). Two well defined and empirically supported models have been used to assess the adverse effect of psychosocial stressors at work.…”
Section: Introductionmentioning
confidence: 99%
“…and meta-analyses on various stressors in relation to obesity, type 2 diabetes and liver disease are summarised in table 3 23,96,124,125,131,132,[135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] . The relative risk estimates have varied between 1.1 and 1.5 for markers of stress, such as PSTD, workplace bullying, psychological distress, job strain, long working hours, effort-reward imbalance and stressful life events.…”
Section: The Scale Of the Problem (A Horizontal Comparison) Findings ...mentioning
confidence: 99%
“…Most of the previous research on work-related exposures and risk of DM has focused on job strain (2,9,28,29), with a smaller body of research focused on long working hours, burnout, effort-reward imbalance, job insecurity, and bullying and violence (4–8). The studies examining the relationships of overqualification and health and well-being outcomes have overwhelmingly used subjective measures of overqualification (perceived overqualification) (10).…”
Section: Discussionmentioning
confidence: 99%